Ultrasensitive aptasensor using electrospun MXene/polyvinylidene fluoride nanofiber composite for Ochratoxin A detection - Al Dhahebi, Adel Mohammed; Jose, Rajan; Mazli, Mustapha; Mohamed Shuaib, Mohamed Saheed (Elsevier, 2022)
Ochratoxin A (OTA) has harmful effects to human and animal health; therefore, sensitive and selective detection of OTA is highly demanded. Herein, an ultrasensitive electrochemical aptasensor electrode comprising electrospun MXene/polyvinylidene fluoride (Ti3C2Tx/PVDF) nanofiber composite is presented. Addition of Ti3C2Tx up to 13% effectively increased the fiber diameter and lowered the β-phase of PVDF nanofibers, consequently lowering the charge transfer resistance. The nanofiber composite is then coated on the screen-printed carbon electrode to chemically functionalized with saline and aldehyde groups for efficient aptamer loading. The optimized aptasensor demonstrated sensitive detection of OTA over the dynamic concentration range from 1 fg mL−1 to 1 ng mL−1 with a limit of detection of 2.15 fg mL−1 and quantification limit of 6.52 fg mL−1, with high selectivity. The aptasensor could detect the OTA at femtogram per milliliter concentration in grape juice samples, demonstrating its enormous potential for OTA detection in food industry.